Overcoming barriers to the treatment of binge eating - Bilić, Sally Sophie; Stadler, Johanna; Bauer, Stephanie (Binge eating, 2020)
Despite the significant burden of illness associated with binge-eating disorder, only a minority of affected individuals seek and receive adequate professional treatment. In this chapter, we provide an overview on the various individual, structural, and practical barriers that hinder help-seeking and uptake of treatment for eating disorders in general and binge-eating disorder in particular. Individual factors may include limited self-recognition, a lack of mental health literacy, shame, and stigmatization as well as high ambivalence to change. Socioenvironmental factors may include a lack of social support, stereotypes, and misconceptions. In addition, the limited availability, accessibility, and affordability of treatment play a major role. Finally, a lack of knowledge and experience among health professionals from outside the eating disorders field may contribute to delayed diagnosis and suboptimal treatment. We will describe strategies to increase the reach of preventive and therapeutic interventions. These include, for instance, advocacy efforts and initiatives on the health policy level, screening tools for the early detection of eating disorders, and technology-enhanced interventions to provide support to currently underserved populations. Finally, priorities for future research on barriers and facilitators to care in the eating disorders field are discussed.
Gesehen am 10.03.2021